Real-time sonoelastography evaluation of the Achilles tendon following ultrasound-guided platelet-rich plasma injection and eccentric exercise for the treatment of refractory Achilles tendinopathy. (August 2019) - Ooi, Chin Chin; Schneider, Michal; Malliaras, Peter; Png, Meng Ai; Chadwick, Martine; Jones, Donna; Venkatanarasimha, Nanda; Connell, David
The objective of this study was to investigate the feasibility of using sonoelastography to depict Achilles tendon stiffness after platelet-rich plasma injection and eccentric exercise for chronic Achilles tendinopathy, and to correlate sonoelastography findings with clinical outcome up to 12 months after treatment. Forty-five Achilles tendons from 45 patients (33 males, 12 females; mean age 51 years) were examined using sonoelastography and ultrasound at baseline, 4–6 weeks, 6 months and 12 months post-treatment. The strain ratio (between Achilles tendon and Kager's fat) during sonoelastography was obtained. The proportion of tendons with hypoechogenicity and neovascularity were documented. Clinical outcomes were assessed by the Victorian Institute of Sport Assessment-Achilles questionnaire and correlated with sonographic findings. The Victorian Institute of Sport Assessment-Achilles improved significantly from 38.4 (±14.1) at baseline, 77.2 (±12.5) at 6 months ( p < 0.001) to 81.2 (±10.8) at 12 months ( p < 0.001). The strain ratio values were 2.16 (±1.02) at baseline, 2.03 (±0.67) at 4–6 weeks, 1.81 (±0.62) at 6 months and 1.19 (±0.34) at 12 months with a significant reduction observed at 6 months (p = 0.006) and 12 months ( p < 0.001). At 12-month evaluation, none of the tendons regained a normal echotexture. Strain ratio demonstrated a moderately good inverse correlation with Victorian Institute of Sport Assessment-Achilles (r = −0.610, p<0.001) while B-mode and Doppler ultrasound did not show a significant correlation (r = −0.041, p = 0.817, and r = −0.116, p = 0.514). Achilles tendon stiffness shows moderately good correlation with clinical symptom at 12-month post-treatment. Sonoelastography using strain ratio could be a promising ancillary tool for monitoring Achilles tendon healing after treatment.